Assessing the Customer-Based Impact of Up-Selling Versus Down-Selling. (August 2018) - Norvell, Tim; Kumar, Piyush; Contractor, Sunil
This article evaluates customers' postpurchase attitudinal and behavioral responses to two suggestive selling strategies employed in retail establishments: up-selling and down-selling. Our findings are based on a field study conducted among 2, 381 customers from a large, national casual dining chain. We then followed up with 352 customers 1 month later to determine the impact of the suggestive selling strategy on future visitation. We find that while up-selling did improve short-term revenues, it had an adverse effect on customers' attitudinal responses which resulted in a reduction in future brand patronage. Conversely, down-selling did not compromise short-term revenues as is commonly thought, and also led to a superior attitudinal response and increased brand patronage. We demonstrate that the effect of the suggestive selling strategy on satisfaction and brand loyalty is chain mediated through value and quality. Finally, our findings suggest that, under certain circumstances, employing a down-selling strategy may lead to superior long-term revenues.